Pengaruh Brand Trust dan Kualitas Jasa terhadap Loyalitas Merek PT. Lion Express (Studi Kasus Pada Agen Jalan Asia) - Fandy Susanto; Thomas Sumarsan Goh; Wily Julitawaty; Syawaluddin Syawaluddin (J-MAS (Jurnal Manajemen dan Sains), 2022)
Brand trust is the desire of customers to trust and believe in a brand with the risks faced because expectations of the brand will lead to positive results. Service quality is an effort to fulfill customer desires and the accuracy of service delivery in order to meet customer expectations. Brand loyalty is a term in marketing to describe how strong a consumer's preference for a brand is when compared to other brands. Analysis of the data used is multiple linear regression. The sampling technique used is saturated sampling. Data collection techniques using a questionnaire. The research scale uses a Likert scale. Partial research results, brand trust has no effect on brand loyalty PT. Lion Express. Partially, service quality has an effect on brand loyalty of PT. Lion Express. Simultaneously, brand trust and service quality affect the brand loyalty of PT. Lion Express.